Integrated Reporting and Its Role in Reducing the Asymmetry of Accounting Information for Investors - Muna Hameed Saadoon (International Forum of Researchers and Lecturers, 2025)
Integrated reports represent a disclosure of the vision, mission and strategy of companies towards achieving their current and future goals